A Sociolinguistic Analysis of Register Usage by Members in the “Ikan Hias Kediri (Ihk) *Reborn*” Fish Trading Group In Facebook - Fekaliza Deprin Suharyanto; Salma Cindyaisya; Yuca Dewi Kurniawati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2024)
The Facebook buying and selling community